Prospective study of maternal outcomes in primigravida with gestational diabetes mellitus in a tertiary care centre Venjaramood, Thiruvananthapuram - Kuriakose, Lency S.; Nair, Bhavani L.; Radha, Prameeda P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The prevalence of Gestational diabetes mellitus (GDM) is on the rise. Understanding the various outcomes of it is essential to face this challenge. The aim of the study was to understand the maternal outcomes of GDM in primigravida and to compare the maternal outcomes in primigravida with GDM and without GDM. Methods: This prospective study was conducted in the department of obstetrics and gynaecology at Sree Gokulam Medical College and Research Foundation, Venjaramood, Thiruvananthapuram, on 180 primigravida mothers,90 with and 90 without gestational diabetes. GDM was diagnosed with IADPSG criteria using 75 g Oral glucose tolerance test (OGTT). Results: A total of 180 primigravida with singleton gestation, 90 with GDM and 90 without GDM were followed from pregnancy to delivery after fulfilling criteria during study period. 65.6% GDM mothers had good compliance with Medical nutrition therapy (MNT) and exercise. 88.8% of GDM mothers required induction of labour, 13.3% had pregnancy induced hypertension, 12.2% had vulvovaginal candidiasis and 10% had postpartum hemorrhage. Thus, women with GDM on MNT or MNT with insulin had a higher risk of adverse maternal outcomes but was comparable to normoglycemic mothers if they had good compliance to MNT or insulin. Conclusions: Women with GDM had a higher but comparable risk of adverse maternal outcomes as compared to normoglycemic pregnant mothers, if they strictly adhere to MNT with or without insulin reflecting the importance of good treatment compliance.